Abstracts of the South African Renal Congress 2018 (Johannesburg, 11-14 October 2018) - Paget, Graham (African Journal of Nephrology, 2018)
Abstracts of the South African Renal Congress 2018 held in Johannesburg, 11-14 October 2018. Abstracts published as received.